Solvelim_{xto1}frac{(x^{4}-4)}{(x^{2}-3x+2)}

Cabiolab 2021-02-22 Answered

Solve \(\lim_{x\rightarrow 1}\frac{(x^{4}-4)}{(x^{2}-3x+2)}\)

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

odgovoreh
Answered 2021-02-23 Author has 24405 answers

If \(\lim_{x\to a-}f(x)\neq \lim_{x\to a+}f(x)\) then the limit does not exist
\(\implies \lim_{x\to 1+}\frac{(x^{4}-4)}{(x^{2}-3x+2)}= \lim_{x\to 1+}((x^{4}-4)(x^{2}-3x+2)^{1})\)
\(= \lim_{x\to 1+}(x^{4}-4)\times\lim_{x\to 1+}((x^{2}-3x+2)^{-1})\)
\(=(-3)(-\infty)\)
\(=\infty\)
\(\implies \lim_{x\to 1-}\frac{(x^{4}-4)}{(x^{2}-3x+2)}= \lim_{x\to 1-}((x^{4}-4)(x^{2}-3x+2)^1)\) \(= \lim_{x\to 1-}(x^{4}-4)\times \lim_{x\to 1-}((x^{2}-3x+2)^{-1})\) Conclution: the \(\lim\) is diverges

Not exactly what you’re looking for?
Ask My Question
43
 

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more
...